PENGEMBANGAN VIDEO KEGIATANKU PADA MATERI MENULIS NARASI DI SEKOLAH DASAR - Istianatul Ulfa; Nanang Khoirul Umam; Iqnatia Alfiansyah (JUSEDA, 2021)
This development research aims to find out develop videos of my activities on narrative writing material in elementary schools in 3rd grade MI Al Ma'arif Sukomulyo in the 2019/2020 school year. The process of learning development using ADDIE (analysis, design, development, and evaluation) and the result of learning is my activity video (aka vlog) which contain narration writing and daily routine stories. Sources of data in this development research are material experts and media experts, amounting to 4 validators and 28 grade 3 students. The data collection used was the validation of learning media and tests of student learning outcomes. With data analysis, namely, analysis of the validity of learning media, analysis of the practicality of learning media and the effectiveness of learning media. Based on the results of the descriptive analysis of the validation results, it was found that the development of my activity videos on narrative writing material in Elementary Schools met the following good criteria: material 2 with a total average assessment of 100%, and a percentage of 100% by media experts 1 and a percentage of 79.2% by media experts 2 with a total average rating of 89.6% which is categorized as valid and can be used in the process learning, b) being categorized as practical from the results of the analysis in the practicality of learning media by the validators shows that the media can be used with little or no revision. c) whereas in the learning outcome test, students who obtained a score of ≥70 were 27 of the 28 students with a percentage of 96,42% which were categorized as effective for use in the learning process.